Idaho road & recreation atlas (Benchmark Maps, 2021)
"Benchmark has extensively revised the Boise area metro map and the Recreation Guide has been thoroughly updated. And the atlas still has all of the features people love: generous page-to-page overlap, a usable GPS grid, and field-checked accuracy. Idaho's boundless recreational opportunities and beautiful scenery come into precise focus on every page of the Idaho Road and Recreation Atlas. The improvements in the new sixth edition follow new field-checking efforts and data enhancements. The Landscape Maps now show ground-cover detail at a very high resolution. It's easy to see immediately whether an area is forested, cultivated, lava flow, or scrubland." -- Amazon.